Response of Maize Crop to Spatial Arrangement and Staggered Interseeding of Haricot Bean - Hirpa, Tamiru (International Journal of Environment, 2014)
Field studies conducted to determine the effects of intercrop row arrangements and staggered intercropping of haricot bean (Phaseolus vulgaris L.) on the performances of maize (Zea mays L.) crop at Hallaba and Taba areas in 2013 cropping season, southern Ethiopia, revealed that there were significant effects of cropping patterns and staggered interseeding of the legume component on growth and yield components of maize crop. Significant interaction of row arrangement × intercropping time of haricot bean was observed with respect to leaf area index (LAI) of the maize crop. Increasing trends of LAI of maize crop were observed as interseeding of haricot bean was delayed for 3 weeks after maize (WAM) that stabilized during the 6 WAM interseeding time. Maize stover production was significantly high at 1:2 row ratio and delaying of the undersowing haricot bean in the already established maize crop for 6 weeks, 10.94 tha-1 and 11.39 t ha-1, respectively. Maize grain yield showed a significant variation with respect to the staggered sowing of haricot bean, whereby the highest (3.99 t ha-1) being recorded when haricot bean intercropping was delayed for 21 days after maize planting. The data of this study revealed that the larger maize plant canopy providing larger photosynthetic area, attained when haricot bean interseeding was delayed, probably resulted in higher grain yield of maize. DOI: http://dx.doi.org/10.3126/ije.v3i3.11072 International Journal of Environment Vol.3(3) 2014: 126-138